Pengetahuan Budaya Nginang Oleh Masyarakat Dukuh Tegalsari, Klaten dan Desa Pakuncen, Serang Sebagai Obat - Naufal, Muhammad Afi; Apsari Nisa Mumpuni; Sulyanah; Niken Ayu Safitri; Ghina Chairunnisa; Widya Lendra; Muhammad A. Ikhram; Riska; Priyanti; Ardian Khairiah; Des M. (Prosiding Seminar Nasional Biologi, 2021)
Indonesian people have long known betel leaf as an ingredient for betel nut with the belief that betel leaf can strengthen teeth, heal minor wounds in the mouth, eliminate bad breath, stop bleeding gums, and mouthwash. The purpose of this research is to find out the culture of nginang by the people in the Dukuh Tegalsari, Klaten and Pakuncen Village, Serang. The method used is descriptive with qualitative and quantitative analysis. Data collection techniques using interviews and questionnaires. The results showed that 5 plant species and 5 families were used in nginang culture in both survey locations. Calculation of RFC (Relative Frequency of Citation) in both locations shows betel (Piper betle L.) as a plant species with the highest value of 1 and the lowest 0.18 in tobacco (Nicotiana tabacum L.) and gambier (Uncaria gambir Roxb.) plant in Dukuh Tegalsari. Betel leaf (P. betle) had the highest percentage in both locations with a part value used of 100% when compared to the other four plant species. Clove flower (Syzygium aromaticum L.) has the smallest percentage of used portion value of 5% in Dukuh Tegalsari. The people of Dukuh Tegalsari and Desa Pakuncen have the same ingredients used in the nginang culture where betel leaf (P. betle) is the main ingredient of the nginang culture as medicine.